Age-Related Changes in Magnesium Status within Oil Palm Cultivation in Eastern Amazon - de Jesus Matos Viégas, Ismael; de Souza, Antonia Erica Santos [UNESP]; Costa, Milton Garcia [UNESP]; de Oliveira Ferreira, Eric Victor; do Nascimento, Layana Gomes; Silva, Dioclea Almeida Seabra; de Oliveira Neto, Cândido Ferreira (Friends Science Publishers, 2024)
The purpose of this study was to describe magnesium (Mg) concentration, accumulation, and export, as well as Mg use efficiency and nutrient requirements in oil palm (Elaeis guineensis Jacq.) plants of different ages. For this, an experimental field comprised a completely randomized design (CRD) with seven treatments of plant ages (from 2nd to 8th year) was conducted. We technically assessed numerous vegetative and reproductive components at both plants age. Plant tissue sample were collected and sent to laboratory for extraction of Mg content. The data were submitted to the variance analysis (P < 0.05) and to regression model adjustments. Our results showed that plant age influenced the dynamics of Mg, mainly its concentrations in the reproductive organs. Mg showed greater accumulation and export with increasing plant age. The capacity of reuse in senescent tissues provided greater Mg use efficiency and requirement. Mg should be supplied according to plant age and the total quantity extracted and recycled as well as the Mg content in the soil should be considered, besides the quantities exported. Our insights are essential for the management of Mg fertilization in oil palm plantations.
Keywords: Elaeis guineensis; Mg export; Mg immobilization; Mg recycling; Mg use efficiency